Metode Jitu Tahsin Al-Quran 2 Tahun Khatam 30 Jus Al-Quran - Prananosa, Ahmad Gawdy; Yuana, Dika Novri; Umartin, Dodi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the purpose of learning Tahsin Al-Quran and knowing the method of learning Tahsin Al-Quran. Knowing the evaluation of learning Tahsin Al-Quran. This study uses a qualitative type with a phenomenological approach. Data collection techniques include; observation, interviews and documentation, the techniques used in data collection include: observation, interviews, and documentation. Analysis of the data using an interactive model (Miles and Huberman, where the analysis process is carried out simultaneously with the process of observation and interviews as well as direct documentation is analyzed. The results show that; The purpose of Tahsin Al-Uthmani learning at the Qur'an Al Fida Islamic Boarding School is so that students are able to read Al - The Koran properly and correctly in accordance with the makhrojul letters and the rules of tajwid science, namely being able to read the Koran in tartil, fluently, paying attention to the correct legal rules of recitation, and being able to read the Koran smoothly. Then the use of the Ottoman method in learning Tahsin Al -The Qur'an at Pesantren Qur'an Al Fida Bengkulu can be declared effective and can be a good guide for learning Al-Qur'an Tahsin, of course, accompanied by a lot of practice and reading practice. effective in learning Tahsin Al-Qur'an making it easier for students to read the Qur'an well and right. Keywords: Learning Method, Tahsin Al-Qur'an